Outcomes in women over 40 years old - Duarte, Carlos (2014)
Nowadays, motherhood tends to be shifted to the later years of reproductive life. However, many women are not aware that their fertility rate decreases dramatically over time in the latest years of fertility. When couples do not achieve a pregnancy to term, they turn to assisted reproductive techniques, which become even more costly when the couple’s age is higher. Factors leading to infertility are not clearly understood; nevertheless, several studies aim to variations in apolipoprotein levels in folicular fluid and serum variations of follicle stimulating hormone (FSH). According to researchers in clues to infertility, variations in apolipoprotein and FSH levels and number of embryos transferred may be used as standards in order to obtain better results with assisted reproduction.